(untitled) (Economic and Political Thought, 2011)
The article aims to present the existing global financial architecture against a background of global architecture and directions of necessary reforms in the context of global economy protection against the global financial and economic crises. The future global financial architecture on the one hand should be based on broader legitimization and on the other hand should provide higher effectiveness of preventing and fighting with crises. The main reason for the failures of the present global financial architecture in this field is its inability to keep up with the development of globalization processes that are a source of global macroeconomic imbalance as well as new risks for stability of the global financial system. It is necessary to introduce changes of the liberalizing and regulating global financial architecture into a model of coordinated market economy – also on a global scale. In the new architecture, a bigger role should be played by the countries with the highest economic potential: the so called emerging markets such as China, India, Brazil, etc. The reforms that are being implemented in the global financial institutions – the IMF and the World Bank – are going exactly in this direction. Moreover, it is necessary to consider the development of a global financial institution sharing both liberalizing and regulating powers. The institution should condition financial liberalization on accepting the adopted adequate regulatory solutions by the member states.